2019
DOI: 10.1002/adfm.201900129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Large‐Area Atomically Thin BiOI Crystals with Highly Sensitive and Controllable Photodetection

Abstract: Compared to the most studied 2D elements and binary compounds, ternary layered compounds with more adjustable physical and chemical properties have exhibited potential applications in electronic and optoelectronic devices. Here, 2D ternary layered BiOI crystals are synthesized first with a domain size up to 100 µm via space-confined chemical vapor deposition. The photodetectors based on the as-grown BiOI nanosheets demonstrate high sensitivity to 473 nm light. The I on /I off ratio and detectivity of BiOI phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 50 publications
(56 reference statements)
2
93
0
Order By: Relevance
“…Thus both Ag and B1g vibrational modes behave “blue shift” with thickness increase. We attribute this phenomenon to the unique chain‐like structure and the increased long‐range Coulombic interaction in thicker samples, which is also observed in recently reported 2D Sb 2 Se 3 and BiOI crystals 21,49. In addition, representative Raman intensity maps of A g and B 1g modes of a typical Sb 2 Se 3 triangular flake are given in Figure 4c, indicating a highly uniform crystal structure over the whole flake.…”
Section: Resultssupporting
confidence: 80%
“…Thus both Ag and B1g vibrational modes behave “blue shift” with thickness increase. We attribute this phenomenon to the unique chain‐like structure and the increased long‐range Coulombic interaction in thicker samples, which is also observed in recently reported 2D Sb 2 Se 3 and BiOI crystals 21,49. In addition, representative Raman intensity maps of A g and B 1g modes of a typical Sb 2 Se 3 triangular flake are given in Figure 4c, indicating a highly uniform crystal structure over the whole flake.…”
Section: Resultssupporting
confidence: 80%
“…In other words, stronger vdWs force can suppress the vibration of atoms. With increasing the layer number, A1g2 would stiffen causing the increased wavenumber 17,24. These results clearly demonstrate the engineered electronic properties for the ultrathin BiOBr nanoflakes.…”
Section: Figurementioning
confidence: 60%
“…Barium oxyhalide is a typical multicomponent metal halide oxide, which belongs to group V‐VI‐VII, with high chemical stability, nontoxicity, and corrosion resistance . Most recently, Feng et al have reported a facile synthesis of large‐area atomically thin BiOI by space‐confined chemical vapor deposition (CVD), and for the first time attempted a visible light photodetector based on 2D BiOI nanosheets with good photo response and high sensitivity. Compared with BiOI, BiOCl possesses a relatively big band gap close to 3.2 eV with pronounced photosensitivity, which shows promise for ultraviolet (UV) light detection .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with BiOI, BiOCl possesses a relatively big band gap close to 3.2 eV with pronounced photosensitivity, which shows promise for ultraviolet (UV) light detection . Up to now, most of the BiOCl synthesis works focus on the well‐developed liquid phase method . The surface contamination and low quality of the BiOCl obtained by hydrothermal obstruct their practical application in photoelectric conversion and semiconductor device areas.…”
Section: Introductionmentioning
confidence: 99%